The Relationship Between MRI Signal Intensity Changes, Clinical Presentation, and Surgical Outcome in Degenerative Cervical Myelopathy: Analysis of a Global Cohort. Issue 24 (15th December 2017) - Nouri, Aria; Martin, Allan R.; Kato, So; Reihani-Kermani, Hamed; Riehm, Lauren E.; Fehlings, Michael G.
Abstract : Study Design: Retrospective analysis of prospective data. Objective: To assess the relationship between MRI signal intensity changes, clinical presentation, and surgical outcome in degenerative cervical myelopathy (DCM). Summary of Background Data: Several studies have sought to assess the extent of spinal cord dysfunction and the potential for postoperative neurological recovery through the evaluation of spinal cord signal change on T2-weighted (T2WI) and T1-weighted images (T1WI). There remains ambiguity if T2WI and T1WI signal changes (1) relate to baseline severity, and (2) predict neurological recovery after surgical treatment. Methods: Four hundred nineteen MRIs from two prospective multicenter studies were examined. Images were assessed for the presence, levels, and location of spinal cord signal intensity changes and compared with clinical data. Signal changes were also evaluated for the prediction of 2-year postoperative outcome using mJOA parameters. Results: MRIs were categorized by T1WI and T2WI signal change: no signal change (28.9%), T2WI hyperintensity-only (T2WI-only, 51.8%), and T2WI-hyperintensity and T1WI-hypointensity (T1WI+T2WI, 19.3%). T2WI-hyperintensity was present at multiple levels in 27% of patients overall. Baseline severity increased from no signal change to T2WI-only to T2WI+T1WI ( P  < 0.0001), and there was an incremental increase in the frequency of signs/symptoms. There were no differences in outcomes between no signal change and T2WI-only groups. The presence of T1WI-hypointensity correlated with reduced recovery ratio ( P  = 0.03) and likelihood of an optimal surgical outcome ( P  = 0.005), adjusting for baseline mJOA. A greater number of T2WI-hyperintensity levels was also associated with worse baseline severity ( P  < 0.0001) and recovery ratio ( P  = 0.001). Conclusion: This analysis of a global cohort of DCM patients shows a stepwise trend toward increasing impairment from no signal change to T2WI-hypertensity to T1WI-hypointensity. T1WI signal change indicates more permanent injury, portending decreased functional recovery. T2WI-hyperintensity alone does not predict outcomes. Multiple levels of T2WI-hyperintensity suggest additional tissue injury, correlating with worse clinical impairment and recovery potential. Level of Evidence: 2 Abstract : Supplemental Digital Content is available in the text